Stem Cell Surgery and Growth Factors in Retinitis Pigmentosa Patients: Pilot Study after Literature Review - Limoli, Paolo Giuseppe (Biomedicines, 2019)
To evaluate whether grafting of autologous mesenchymal cells, adipose-derived stem cells, and platelet-rich plasma into the supracoroideal space by surgical treatment with the Limoli retinal restoration technique (LRRT) can exert a beneficial effect in retinitis pigmentosa (RP) patients. Twenty-one eyes underwent surgery and were divided based on retinal foveal thickness (FT) ≤ 190 or > 190 µm into group A-FT and group B-FT, respectively. The specific LRRT triad was grafted in a deep scleral pocket above the choroid of each eye. At 6-month follow-up, group B showed a non-significant improvement in residual close-up visus and sensitivity at microperimetry compared to group A. After an in-depth review of molecular biology studies concerning degenerative phenomena underlying the etiopathogenesis of retinitis pigmentosa (RP), it was concluded that further research is needed on tapeto-retinal degenerations, both from a clinical and molecular point of view, to obtain better functional results. In particular, it is necessary to increase the number of patients, extend observation timeframes, and treat subjects in the presence of still trophic retinal tissue to allow adequate biochemical and functional catering.